Development of system operations models hierarchy on the aggregating sign of system mechanisms - Lutsenko, Igor; Fomovskaya, Elena; Vikhrova, Elena; Serdiuk, Olga (Eastern-European Journal of Enterprise Technologies, 2016)
Now there is a terminological uncertainty concerning such basic cybernetic categories as the mechanism, a product, operation. Such uncertainty, on the one hand, is caused by the fact that these categories, essentially, are interconnected. On the other hand, the object of research has to be defined by the class of solvable task. As the concept “operation” is an abstraction of the highest level, it is necessary to establish compliance between the area of research and the type of operation. That is, there is a need for the decrease of the degree of abstraction, however, the power of the set connected with the concept “operation” has to be reasonable. In the work, compliance between a hierarchical representation of the system mechanism structure which degree of hierarchy is expressed as the aggregating sign, and the power of the registration model of the system operation is established. Identification of operations on the aggregating sign of system mechanisms allows to expand the conceptual cybernetic framework and to systematize problems which are solved in the course of operations research. It is found that the cybernetic operation is the result of the interaction of system products and system mechanisms directed to transformation of input products of the operation to output products of the operation. Definition of the cybernetic operation model as forms of data presentation displaying results of procedural interaction of system products and system mechanisms is given. It is noted that a distinctive feature of the cybernetic operation is a limitation of its duration in time. Definition of the operation and the operation model allows determining the area of developments connected with the statement and the solution of problems in operations research. It is found that the registration model of any sets operation can be presented in the form of two functions comparable to each other: input and output functions. Definition of input and output functions is a necessary and sufficient condition for unambiguous identification of the studied operation concerning its efficiency.